The effectiveness of interactive multimedia software in increasing primary one students' motivations in learning mathematics - Shahnida, Eddie. (Universiti Malaysia Sarawak (UNIMAS), 2004)
This study aims to determine students' motivation level in learning Mathematics through the use of interactive multimedia software as teaching aid. Thirty-six Primary One students of Sekolah Kebangsaan St. Teresa, Kuching participated in this study. The participants were chosen using the stratified random sampling method. Experiments were conducted over a two-week period. The focus of this study is to evaluate the effectiveness of motivational factors (challenge, curiosity, control and fantasy) in increasing students' motivation level in learning Mathematics. A questionnaire was used to collect data. Descriptive (percentages and frequencies) and inferential statistics (One Way ANOVA and Pearson's Co-efficient Correlation) were applied for data analysis. Results revealed that students generally display an average level of motivation, indicating that motivation to learn caused by the use of interactive multimedia software in the classroom does not necessarily increase. Variation in socio-economic status and academic ability had no significant effect on students' motivation level. Of the four motivational factors, only fantasy was deemed motivational by students.